The mRNAs of Prekallikrein, Factors XI and XII, and Kininogen, Components of the Contact Phase Cascade Are Differentially Expressed in Multiple Non-hepatic Human Tissues - Neth, Peter; Arnhold, Marianne; Nitschko, Hans; Fink, Edwin (Thrombosis and Haemostasis, 2001)
Recently RT-PCR studies had demonstrated the expression of plasma prekallikrein (PPK) mRNA in extrahepatic tissues. The questions arose whether that is illegitimate or regular expression, and whether the mRNAs of blood coagulation factors XI and XII, and high molecular weight kininogen, components of the contact activation cascade of blood coagulation are also expressed in non-hepatic tissues. These questions were addressed in the present study by employing quantitative RT-PCR. The relative mRNA levels of the respective proteins determined in 16 human tissues indicate legitimate extrahepatic transcription of at least three of the genes. Transcription of all genes was highest in the liver, but only PPK mRNA was detected in all 16 tissues, especially high levels in pancreas, kidney, testis, spleen and prostate. We conclude from these results that PPK is synthesized in significant amounts in non-hepatic tissues and that this locally synthesized PPK may have special local functions.
Keywords: Extrahepatic expression of contact activation proteins; illegitimate transcription; quantitative RT-PCR; TaqMan technique